Effect of Olive Oil on Hesperidin Nanovesicles in Treatment of Induced Corneal Ulcers in Rabbits, Morphological and Histopathologic Study: Impact of Hesperidin Nanovesicles in Treatment of Corneal Ulcers in Rabbits - Ali, Ahmed; Khallaf, Iman S.A.; Hassan, Abeer S.; Sayed, Marwa A.; Hamdy, Aya; Ali, Magda; Hassanein, Khaled M. A.; El- Badry, Mahmoud; Abdelhakiem, Mohammed A. H. (Iranian Journal of Pharmaceutical Sciences, 2024)
Hesperidin (HSP) and Olive oil possess many biological activities that are required for the safe and effective treatment of corneal ulcers. However, the poor aqueous solubility of HSP hinders its topical utilization. This work aims at enhancing the dissolution of HSP and combining the powerful effectiveness of Olive oil in treating corneal ulcers. HSP was isolated from orange peel and described by spectroscopic methods (1H NMR and 13C NMR), then HSP nanovesicles were prepared with and without Olive oil using the ethanol injection method. Nanovesicles were applied topically to rabbits’ eyes in which alkali burn corneal ulcers were induced. After five weeks, histopathological studies were performed. No ulcers were determined after topical application of HSP, and the inclusion of Olive oil returned the eye to its normal conditions. Thus, this study clarified the potential role of the HSP - Olive oil combination in managing corneal ulcers.